The naming of halal food and beverages: A multimodal semiology study - Siti Isnaniah; Tiya Agustina; Muhammad Arief Rochman; Hari Kusmanto (Studies in English Language and Education, 2024)
The culinary business has been flourishing in every city in Indonesia, including Surakarta, Malang, and Tangerang. Consequently, determining the names of products becomes crucial to pique the interest of the public in these offerings. This research is aimed to review the naming of food and beverages using a semiology approach. The research uses a descriptive explanative method. The data in this research are the names of food and beverages. The sources of the data are documents related to names of culinary businesses (food and beverages) in restaurants in Surakarta, Malang, and Tangerang. The data collection was conducted through documentation, observation, and data recording in data format. The data analysis uses referential equivalent, strengthened with semiology theory from Roland Barthes, namely searching for signs, denotative meaning, connotative meaning, and myth. The research indicates that, in general, the names of food and beverages sold in restaurants often contain unconventional elements, including references to ghosts, animals, and other negative connotations prohibited in the Decree of The Head of Badan Penyelenggara Jaminan Produk Halal (BPJPH or the Halal Product Assurance Agency) Number 57 Year 2021. This suggests that the naming of food and beverages in Surakarta, Malang, and Tangerang does not align with the provisions outlined in Decree Number 57 Year 2021, preventing the business owners from obtaining halal certification. The research recommends that the naming of halal food and beverage products adhere to the guidelines set by this decree.